Uncertainties in future energy demand in UK residential heating - Eyre, N; Baruah, P (Elsevier, 2016)
Fossil fuels are the main source of space heating in the UK, and therefore climate mitigation implies a systemic change in space heating systems. The challenge is difficult because of an inefficient building stock and high penetration of natural gas. We present new quantified scenarios for residential energy use in the UK to 2050. With minimal policy intervention the UK will remain locked into a gas based heating system, which would conflict with the policy goal of decarbonisation. However, there is a range of scenarios in which this is avoided. A system heavily reliant on heat pumps powered by low carbon electricity is UK policy makers' currently preferred alternative. We conclude that some shift in this direction is likely to be required, but complete reliance on this solution raises a number of problems. Greater use of energy efficiency and biomass can also play a significant role. These options have different risks, but a more diversified strategy would be more prudent. We conclude that the future of UK residential space heating is very uncertain, but meeting low carbon heating goals is better conceptualised as reducing reliance on gas rather than necessarily mass electrification. Our analysis has implications for any country with high use of fossil fuels in space heating and ambitious decarbonisation goals.